BOTANICAL INVESTIGATIONS IN MEXICO - MARTINEZ, MAXIMINO (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1973)
The medium recommended consists of Bacto-tryptose 2, NaCl 05, Na citrate 05, agar 3 g, and dist water 100 ml The mouth of fiat rectangular bottles containing 15 ml of this medium is covered with thick paper and sterilized at 15 lbs pressure Then 1
BOL SOC GEO EST REP MEX
Keywords: BOTANICAL INVESTIGATIONS, MEXICO; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL